INTERACTION COMPETENCE IN TEACHING PROCESS - Akbarova Ravzaxon Abdullayevna; Yusupova Maftuna Baxtiyor qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Interaction is needed in the classroom activity. It helps the teaching and learning process run smoothly and it can increase learners’ communicative. It tells how the students have interaction among them and teacher even with the whole class. The aim of this study is giving the teacher some suggestions to achieve classroom interaction in the teaching reading. It offers some strategies to improve the interaction in the classroom. Then it can be applied in the teaching of reading. Several previous studies about classroom interaction which is show the different outcome happen. Several studies show that classroom interaction is important in the teaching learning process. Some studies show that the students’ interaction happens in the classroom. By using classroom interaction, the students are more active in the learning process. The result of the study concludes that classroom interaction has important role in the teaching and learning process.